2018
DOI: 10.1021/acs.nanolett.8b03850
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of Plasmonic Chiral Radiative Local Density of States with Cathodoluminescence Nanoscopy

Abstract: Chiral light-matter interactions as an emerging aspect of quantum optics enable exceptional physical phenomena and advanced applications in nanophotonics through the nanoscale exploitation of photon-emitter interactions. The chiral radiative properties of quantum emitters strongly depend on the photonic environment, which can be drastically altered by plasmonic nanostructures with a high local density of states (LDOS). Hence, precise knowledge of the chiral photonic environment is essential for manipulating th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
56
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(57 citation statements)
references
References 35 publications
1
56
0
Order By: Relevance
“…We obtained well-defined nanostructures with reproducible sizes and gap distances (see the SEM image in Figure 4a). Previous reports on the experimental characterization of the optical near-field chirality relied on near-field optical microscopy (SNOM) [17,26,27] and cathodoluminescence [20]. Here, we use a photosensitive this technique is about 20 nm [28] and can map plasmonic hot spots [29].…”
mentioning
confidence: 99%
“…We obtained well-defined nanostructures with reproducible sizes and gap distances (see the SEM image in Figure 4a). Previous reports on the experimental characterization of the optical near-field chirality relied on near-field optical microscopy (SNOM) [17,26,27] and cathodoluminescence [20]. Here, we use a photosensitive this technique is about 20 nm [28] and can map plasmonic hot spots [29].…”
mentioning
confidence: 99%
“…[50] Previous studies have reported to explore metal nanostructures in detail by CL detection and mapping with deep-subwavelength resolution precision. [51,52] Here, CL measurements were also performed to explore the radiation mode from the metasurface.…”
Section: Doi: 101002/smll202003539mentioning
confidence: 99%
“…However, the quantum yield of untreated monolayer TMDCs turns to be rather low (typically less than 1%) at room temperature, resulting in a weak photoluminescence (PL) behavior [8,14,15]. Various approaches have been developed and introduced to reinforce the emission of monolayer TMDCs, including integration of noble metal nanoantenna via localized surface plasmon [16][17][18][19][20][21][22][23][24], chemical modification [14,25] and construction of heterostructures with additional high-absorption perovskite materials [26,27]. While some improvements have been observed, there are some realistic limitations using these methods.…”
Section: Introductionmentioning
confidence: 99%